Cuantificación voltamétrica de plomo y cadmio en papa fresca (2016)
The presence of heavy metals in food has been reported as one of the high impact problems due to their toxicity and human health problems. The square wave voltammetry method (VOC) was validated for quantification of cadmium and lead in potato. This study was conducted using as buffer solution Britton-Robinson (BR, pH 4.8), glassy carbon as working electrode, Ag / AgCl as reference electrode and platinum as counter electrode. The application of VOC technique was performed in tubers from the central supply of Tunja (Boyacá-Colombia). The analysis of variance showed no statistical difference validation, analysis was performed with a confidence level of 94.5% to 92.0% for cadmium and lead. The concentration of these metals in the samples analyzed were within the range of 0.111 to 0.304ppm exceeding the limits set by national and international standards for tubers of human consumption.